Outbreak of KPC-2 producing Serratia marcescens MDR in a tertiary hospital in the Midwest region, Brazil (Research, Society and Development, 2021)
About 700,000 deaths per year worldwide are caused of Healthcare-related infections (HAI). Result in significant patient morbidity and mortality, being is ranked the fourth leading cause of death in Brazil. Usually, HAI are caused by multidrug-resistance microorganisms (MDR), as well as Serratia marcescens, that is associated with healthcare-related infections causing high patient mortality and morbidity. This paper describes an outbreak of S. marcescens MDR carrier gene blaKPC-2 in a university hospital, with the need to broadly combat horizontal transmission of this bacterium between patients, as well as the need to optimize treatment with other antimicrobial classes due to resistance of this microorganism to polymyxins. Ten isolates were analyzed for the presence of carbapenemic resistance gene blaKPC-2. This gene was detected in all isolates, with a corresponding high patient mortality rate, highlighting the importance of its molecular detection, which corroborates the resistance of S. marcescens to carbapenem antibiotics. The detection of this gene is necessary due to the importance to broadly combat horizontal transmission of this bacterium between patients, as well as the need to optimize treatment with other antimicrobial agents due to its resistance to polymyxins.